Inducing Better-Facilitated EFL Writing Learning Dynamics with an Enlightenment of Collaborative Writing Strategy - Wijaya, Kristian (Journal of Language and Literature Studies, 2023)
Abstract To better help globalized EFL learners withstand a wide variety of stumbling blocks residing in these modern second language writing learning enterprises, writing instructors should devise a learner-oriented learning approach where writers strongly establish more robust collaborative networking to successfully achieve their desired writing learning goals. A collaborative writing strategy plays an indispensable role to attain this coveted writing learning objective where EFL learners can supportively collate their distinctive ideas, perspectives, and strategies to compose more qualified writing compositions. This currently-initiated qualitative study was in support of an annotated bibliography approach to ascertain the credibility, relevancy, and applicability of the particularly-attained research results. To that end, the researcher utilized a document analysis and an open-coding approach to thematically categorize each identical research result generated by 10 already-published collaborative writing strategy journal articles conducted worldwide. The thematically-analyzed research results highly advised globalized second language writing instructors to incorporate a collaborative writing strategy at the inception of regular writing learning dynamics as it functioned as one of the propelling forces for EFL learners to gradually transform into more skilled, enthusiastic, confident, optimistic, and proactive target language writers. Keywords: EFL writing; collaborative writing strategy; annotated bibliography; document analysis